ROS-mediated waterlogging memory, induced by priming, mitigates photosynthesis inhibition in tomato under waterlogging stress - Niu, Lifei; Jiang, Fangling; Yin, Jian; Wang, Yinlei; Li, Yankai; Yu, Xiaqing; Song, Xiaoming; Ottosen, Carl-Otto; Rosenqvist, Eva; Mittler, Ron; Wu, Zhen; Zhou, Rong (Frontiers in Plant Science, 2023)
With global climate change, the frequency and intensity of waterlogging events are increasing due to frequent and heavy precipitation. Little is known however about the response of plants to repeated waterlogging stress events. The aim is to clarify physiological regulation mechanisms of tomato plants under repeated waterlogging stress, and whether Trichoderma harzianum can alleviate waterlogging injury. We identified two genotypes of tomato, ‘MIX-002’ and ‘LA4440’, as waterlogging tolerant and sensitive genotypes, respectively, based on plant biomass accumulation. The two tomato genotypes were subjected to a waterlogging priming treatment for 2 days (excess water for 1 cm above substrate surface) followed by a recovery stage for 2 days, and then a second waterlogging stress for 5 days (excess water for 1 cm above substrate surface) followed by a second recovery stage for 3 days. Leaf physiological, plant growth parameters, and the expression of five key genes were investigated. We found that the two genotypes responded differently to waterlogging priming and stress in terms of photosynthesis, reactive oxygen species (ROS), and osmotic regulatory mechanisms. Waterlogging stress significantly increased H2O2 content of ‘MIX-002’, while that of ‘LA4440’ had no significant change. Under waterlogging stress, photosynthesis of the two genotypes treated with waterlogging priming returned to the control level. However, Trichoderma harzianum treatment during the second recovery stage did not show positive mitigative effects. The plants of ‘LA4440’ with priming showed lower peroxidase (POD) activity and proline content but higher H2O2 content than that without priming under waterlogging stress. Under waterlogging stress with priming as compared to without priming, SODCC2 was downregulated in two tomatoes, and AGR2 and X92888 were upregulated in ‘MIX-002’ but downregulated in ‘LA4440’. Overall, the two tomato genotypes exhibited distinct photosynthetic, ROS and osmotic regulatory mechanisms responding to the waterlogging stress. Waterlogging priming can induce stress memory by adjusting stomatal conductance, sustaining ROS homeostasis, regulating osmotic regulatory substances and key gene expressions mediated by H2O2, and thus alleviate the damage on tomato photosynthesis when waterlogging reoccurred.